High prevalence of sessile serrated adenomas in contemporary outpatient colonoscopy practice. Issue 3 (March 2017) - Bettington, Mark; Walker, Neal; Rahman, Tony; Vandeleur, Ann; Whitehall, Vicki; Leggett, Barbara; Croese, John
Abstract : Background: Sessile serrated adenomas (SSA) are the polyp precursor of 15–20% of colorectal carcinomas. There is debate about their prevalence and increasing discussion about the need for a serrated polyp detection rate as a quality indicator for colonoscopy. Aims: To assess the prevalence of SSA at an outpatient gastroenterology service. Methods: This is a retrospective study of an unselected consecutive series of patients who had an outpatient colonoscopy between April 2013 and May 2014. The colonoscopy reports were reviewed to identify age, gender, indication for procedure, completion, withdrawal time, adequacy of bowel preparation, number, size and location of polyps. The pathology of all polyps was centrally reviewed by a gastrointestinal pathologist. Results: A total of 707 patients underwent colonoscopy within the study period. The mean age of the cohort was 58 years, and 50.6% were female. Polyp(s) were identified in 66.5% of patients. The SSA detection rate was 20.1%, and the adenoma detection rate was 48.0%. SSA detection was associated with longer withdrawal times. Conventional adenoma detection was associated with older age, male gender, longer withdrawal time and a positive faecal occult blood test result. Conclusion: SSA are highly prevalent in an unselected series of patients attending a gastroenterology outpatient department. Identifying and removing these polyps may help prevent interval colorectal carcinoma. This result may serve as a benchmark for a high‐quality colonoscopy service.